Trends in Wordwall Integration for Elementary IPAS Learning: A Systematic Literature Review - Ratih, Dhewi; Purwoko, Budi; Gunansyah, Ganes; Nasution, Nasution; Mariana, Neni (Papanda Publisher, 2025)
The integration of digital media in education has become increasingly important in supporting interactive, engaging, and sustainable learning processes. This study presents a systematic literature review (SLR) of research on Wordwall applications in elementary Natural and Social Sciences (IPAS) learning published between 2021 and 2025. Guided by the PRISMA protocol, 1,659 records were initially identified, of which 33 articles met the inclusion criteria and were analyzed. The review highlights three main findings. First, Wordwall-based interventions significantly improve student motivation, creativity, and conceptual understanding, making it a valuable tool for enhancing learning outcomes in elementary education. Second, bibliometric mapping reveals that the research landscape is growing steadily, with interdisciplinary linkages to education, computer science, and psychology, indicating its broad academic relevance. Third, challenges such as infrastructure gaps, teacher digital literacy, and the risk of overreliance on gamification remain critical obstacles to maximizing Wordwall’s potential. The thematic synthesis shows that creativity and motivational design are dominant research foci, reflecting global educational priorities toward 21st-century skills. However, limited exploration of long-term impacts and large-scale adoption indicates the need for further empirical investigation. This study contributes to the scholarly understanding of digital gamification in education by providing evidence-based insights into Wordwall’s effectiveness and limitations. It also emphasizes the importance of integrating Wordwall within holistic instructional frameworks rather than treating it as a stand-alone solution. Future directions are proposed to guide researchers, practitioners, and policy makers in strengthening Wordwall’s role as a sustainable innovation for improving IPAS learning in elementary schools.